Analysis of the Influence of Taxpayer Awareness and Modernization of Tax Administration on Tax Compliance of MSMEs - Putra, Loist Abdi; Silitonga, Hery Pandapotan; Ambarita, Marthin Hutler; Loist, Christine; Sudirman, Acai (Cita konsultindo, 2024)
Modernization of tax administration, such as implementing e-filing and e-billing systems, has been proven to simplify reporting and paying taxes for MSMEs. In addition, increasing taxpayer awareness through education and socialization about the importance of taxes also increases compliance. This study aims to analyze the effect of taxpayer awareness and modernization of tax administration on taxpayer compliance with MSMEs. The research design used is oriented towards a quantitative approach. Data were obtained through a survey of 150 MSME actors in Pematangsiatar, North Sumatra Province, which were determined using a purposive sampling approach. Then, the collected data were analyzed using multiple linear regression methods. The study results indicate that taxpayer awareness and modernization of tax administration have a positive and significant effect on taxpayer compliance. This finding indicates the importance of government efforts to increase awareness and improve administrative services to support tax compliance. This study recommends strategic steps for the government to strengthen the synergy between tax education and innovation in tax administration services to increase state revenue from the MSME sector.